Pengaruh Tekanan Ketaatan, Materialitas dan Risiko Audit terhadap Ketepatan Judgment Auditor pada Kantor Akuntan Publik di Sumatera Utara - Agustina Agustina (Jurnal EMT KITA, 2020)
The purpose of this study was to determine the effect of compliance, materiality, and audit risk on the judgment of the auditor's judgment on the Public Accounting Firm in North Sumatra. This analysis is based on data obtained from 45 respondents, namely auditors who have senior auditor positions and junior auditors at the Public Accountants office in North Sumatra by distributing questionnaires. This research is census research. The data used is primary data, which is obtained directly from the research subject in the form of respondents' perceptions by circulating the questionnaire in the form of a questionnaire to the respondent. From the number of questionnaires circulated to respondents as many as 52 sheets, only 45 sheets returned with a rate of return reaching 86.53%. Furthermore, the data analysis in this study used multiple linear regression which was processed using a computer program Statistical Product and Service Solution (SPSS) ver 15.0. The results of the study showed that both simultaneously and partially obedient pressure, materiality, and audit risk had an effect on the accuracy of the auditor's judgment at the Public Accounting Firm in North Sumatra. This proves that the higher the pressure of obedience, materiality and audit risk possessed by the auditor, the higher the auditor's judgment.